Restitution - YEO, Tiong Min (Institutional Knowledge at Singapore Management University, 2009)
There was no single ruling or decision of signal importance to the law of restitution in 2008. Instead, there were a number of decisions which tested the boundaries of various aspects of the law, sometimes only incidentally.